Zardoz - Munrow, David 1942-1976 (Twentieth Century Fox Home Entertainment, 2002)
A science-fiction drama which gives a nightmarish glimpse of the world divided into two societies.
Orig.: Großbritannien 1974. - Sprache: engl. - Untertitel: kroat., tschech., dän., finn., hebr., ungar., isländ., norweg., poln., portug., schwed., türk., engl. for the hearing impaired
Keywords: Feature films; Science fiction films